Investigating the impact of microcalcification size and volume on collagenous matrix and tissue mechanics using a tissue-engineered atherosclerotic cap model - Imke L. Jansen; Deniz Șahin; Frank J. H. Gijsen; Frank J. H. Gijsen; Eric Farrell; Kim van der Heiden (Frontiers in Cardiovascular Medicine)
Atherosclerotic plaque rupture can lead to thrombotic cardiovascular events such as stroke and myocardial infarction. Computational models have shown that microcalcifications (calcified particles with a diameter < 50 μm) in the atherosclerotic plaque cap can increase cap tissue stresses and consequently contribute to plaque rupture. Microcalcification characteristics, such as particle size and volume fraction, have been implicated to affect cap stresses. However, the effect of these characteristics on tissue mechanics within a collagenous matrix, has not been investigated experimentally. In this study, we employ a tissue-engineered model of the atherosclerotic plaque cap with human myofibroblasts to assess the impact of microcalcification size and volume fraction on cap mechanics and rupture. To mimic human microcalcification size and volume, hydroxyapatite microparticles, in two size ranges (diameter up to 5 μm or up to 50 μm) and two volumes (1 v/v% and 5 v/v%) were incorporated homogenously throughout the tissue-engineered model. 5 v/v% of particles caused a significant lowering of the mechanical properties as was shown by a decrease in stiffness and ultimate tensile stress under uniaxial tensile loading. Additionally, the 5 v/v% of hydroxyapatite particles, in both size ranges, caused a reduced tissue compaction during culture. This might indicate that hydroxyapatite particles influence mechanobiological processes governing tissue organisation and consequent tissue mechanics. These experimental data support computational findings regarding the detrimental role of microcalcifications on cap rupture risk and highlight the importance of volume fraction. Furthermore, this study indicates an additional importance to look at the interplay between calcification, its effect on plaque cap-resident cells and the consequent effect on tissue mechanics.